PENYERAPAN ION LOGAM Cr(III) DAN Cr(VI) DALAM LARUTAN MENGGUNAKAN KULIT BUAH JENGKOL (Pithecellobium jiringa (JACK) PRAIN.) - Chaidir, Zulkarnain; Hasanah, Qomariah; Zein, Rahmiana (Universitas Andalas, 2015)
Jengkol shells (Pithecellobium jiringa) an agricultural waste from typical Indonesian plant has been investigated for its ability to absorb heavy metal ions Cr VI and Cr III . Effect of pH, concentration, contact time, mass and the speed of stirring biosorben studied by extraction method. Concentration of metal ions Cr VI and Cr III was measured using Atomic Absorption Spectrophotometer (AAS). The optimum conditions for metal ion uptake of Cr VI occurs at pH 4, the concentration of 7000 mg/L, contact time of 60 minutes, 0.1 g biosorben mass and stirring speed 100 rpm. For the metal ions Cr III wa obtained conditions optimum at pH 5, the concentration of 1500 mg/L, contact time of 60 minutes, 0.1 g biosorben mass and stirring speed 100 rpm. Functional groups contained in the jengkol shells analyzed by Fourier Transform Infra Red (FTIR). Data equilibrium uptake of metal ions Cr VI and Cr III by the jengkol shells analyzed using two isotherm models , namely Langmuir and Freundlich isotherm models . The absorption of both the metal ions tend to follow the Langmuir isotherm models in which the absorption capacity of metal ions obtained for Cr VI ) and Cr III is 24.9376 mg / g and 39. 0625 mg /g . The optimum condition was applied to study the river Batang Arau at Padang city obtained a capacity of 15.065 mg/ g with 45 efficiency, 94 % for the uptake of metal ions Cr (total).